NUTRITIONAL EDUCATION AND MEASUREMENT OF NUTRITIONAL STATUS TO CHILDREN IN STUNTING PREVENTION EFFORT DURING THE COVID-19 PANDEMIC - Selvia Febrianti; Nurasmi Nurasmi; Agus Purnamasari; Nurul Hidayatun Jalilah (JCES (Journal of Character Education Society), 2021)
One of the government's responsibilities is to ensure that citizens, including children under five, receive basic health services. Basic services for toddlers are usually carried out at the Posyandu. However, at this time the posyandu service was temporarily suspended according to government policy due to the pandemic conditions. Monitoring the growth and development of toddlers during the pandemic must still be carried out. This community service activity aims to increase knowledge and the role of the community to prevent stunting in toddlers. The method used is anthropometric measurements to determine the nutritional status of children under five. then assess the mother's knowledge related to stunting with pretest - posttest, and provide counseling about stunting. The results of the service activities that have been carried out show that of the 45 toddlers measured, 33 (73.3%) were under the category of normal height, and 12 (26.6%) were under the category of stunting. Knowledge of under-five mothers about stunting increased after being given health education. Mothers are advised go to posyandu to monitor their child's development and growth. However, during the COVID-19 pandemic, mothers can monitor their children's growth and development independently at home with the Maternal and Child Health handbook.